Source Base of Research of Pedagogical and Cultural-Enlightening Activity of the Society «Prosvita» in Podillia Region (1906-1923) - Bohdan Kryshchuk (Pedagogical Discourse, 2013)
The analysis of the funds of Central state archive of higher bodies of power and management of Ukraine (Kyiv), Central state historic archive of Ukraine (Kuiv), Central state archive-museum of literature and arts of Ukraine (Kyiv), State archive of Khmelnytskyi and Vinnytsia regions as for the subject of availability of materials on revealing of pedagogical and cultural-enlightening activity of the society «Prosvita» in Podillia region in 1906-1923 has been done in the article. It is determined, in particular, that study of the materials of the funds of above mentioned archives allows us to reveal the content and the forms of pedagogical and cultural-enlightening activity of the society, its influence on the national consciousness formation, the role of the society «Prosvita» in the development of education through the spreading of the libraries-reading halls, revealing of educational establishments by the members of the society, organization of work of different educational-professional courses etc.